2010
DOI: 10.1098/rstb.2009.0294
|View full text |Cite
|
Sign up to set email alerts
|

Testicular postgenomics: targeting the regulation of spermatogenesis

Abstract: Sperm are, arguably, the most differentiated cells produced within the body of any given species. This is owing to the fact that spermatogenesis is an intricate and highly specialized process evolved to suit the individual particularities of each sexual species. Despite a vast diversity in method, the aim of spermatogenesis is always the same, the idealized transmission of genetic patrimony. Towards this goal certain requirements must always be met, such as a relative twofold reduction in ploidy, repackaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 142 publications
2
30
0
Order By: Relevance
“…However, the biogenic mechanisms and function of these ncRNAs remain unknown. Previous studies have suggested that the ncRNAs in testis are involved mainly in gene regulation at the posttranscriptional and translational levels during spermatogenesis (34,35). The activities of several autosomal ncRNAs have been associated with the initiation and maintenance of meiotic sex chromosome inactivation, an important gene-silencing process that is established at midpachytene stage and persists to the postmeiotic phase of spermatogenesis (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, the biogenic mechanisms and function of these ncRNAs remain unknown. Previous studies have suggested that the ncRNAs in testis are involved mainly in gene regulation at the posttranscriptional and translational levels during spermatogenesis (34,35). The activities of several autosomal ncRNAs have been associated with the initiation and maintenance of meiotic sex chromosome inactivation, an important gene-silencing process that is established at midpachytene stage and persists to the postmeiotic phase of spermatogenesis (36).…”
Section: Discussionmentioning
confidence: 99%
“…The present review focuses on spermatogenesis-related proteomics in our laboratory and complements other reviews. [16][17][18][19][20] This review aims to improve our understanding of normal spermatogenesis and the cause of abnormalities in spermatogenesis and offers an interpretation of the regulatory mechanisms underlying male fertility and infertility.…”
Section: Introductionmentioning
confidence: 99%
“…These include the use of proteomics and genomics (Calvel et al 2010) and mouse genetic models (Verhoeven et al 2010) to As depicted in figure 1c which summarizes different cellular events that occur during spermatogenesis, it is obvious that some of the events listed on the right panel, such as spermiogenesis and its related cellular processes (e.g. spermatid adhesion to Sertoli cells) can become prime targets to disrupt spermatogenesis, leading to male infertility.…”
Section: Spermatogenesis: the Presentmentioning
confidence: 99%